Religion in Motion: Cohesion, Transformation, and Agency in a Global Age - Busro, Busro (UIN Sunan Gunung Djati Bandung, 2025)
This editorial note situates the articles in Religious: Journal of Religious and Cross-Cultural Studies, Vol. 9 No. 1 (2025), within broader global debates on religion, culture, and social change. It argues that religion, far from receding under secularization and globalization, continues to function as an adaptive social infrastructure. Drawing on case studies from Indonesia (Bali, Toraja, Maluku, Papua) and comparative contexts (Ghana, Rwanda, Europe, and beyond), the contributions collectively highlight five interrelated themes: religion as a framework for social cohesion and conflict resolution, the transformation and re-enchantment of sacred spaces, women’s agency and visibility in religious life, religion’s ambivalent role in radicalism and security, and the historical reinvention of traditions as cultural memory. By weaving together classical theories with contemporary phenomena—including digital media, commodification, and gendered visibility—this issue demonstrates the continued relevance of religion in negotiating identity, fostering peace, and sustaining plural societies in a global age.